Whole-genome experimental identification of insertion/deletion polymorphisms of interspersed repeats by a new general approach - Mamedov, Ilgar Z. (Oxford University Press, 2005)
A new experimental technique for genome-wide detection of integration sites of polymorphic retroelements (REs) is described. The technique allows one to reveal the absence of a retroelement in an individual genome provided that this retroelement is present in at least one of several other genomes under comparison. Since quite a number of genomes are compared simultaneously, the search for polymorphic REs insertions is very efficient. The technique includes two whole-genome selective PCR amplifications of sequences flanking REs: one for a particular genome and another one for a mixture of ten different genomes. A subsequent subtractive hybridization of the obtained amplicons with DNA of a particular genome as driver results in isolation of polymorphic insertions. The technique was successfully applied for identification of 41 new polymorphic human AluYa5/Ya8 insertions. Among them, 18 individual Alu elements first sequenced in this work were not found in the available human genome databases. This result suggests that significant part of polymorphic REs were not identified during genome sequencing and remain to be detected and characterized. The proposed method does not depend on preliminary knowledge of evolutionary history of retroelements and can be applied for identification of insertion/deletion polymorphic markers in genomes of different species.